WOMEN'S EMPOWERMENT IN LANCÔME'S "IT'S WITHIN YOU" CAMPAIGN: AN APPRAISAL ANALYSIS AND CRITICAL DISCOURSE PERSPECTIVE - Novianti Ari Astiti; Fariq Shiddiq Tasaufy (Jurnal Ilmiah Telaah, 2026)
The study investigates the representation of women’s empowerment through evaluative language in the Lancôme “It’s Within You” campaign. The study applies Appraisal Theory (Martin & White, 2005) and Critical Discourse Analysis (Fairclough, 1995) within a qualitative case study design and interpretative paradigm. The data consist of verbal expressions taken from four campaign video domains featuring female brand ambassadors: Penelope Cruz, HoYeon Jung, and Joy Sunday. The analysis examines Attitude, Engagement, and Graduation resources to uncover how evaluative language constructs ideological meanings of empowerment. The findings reveal that empowerment is primarily constructed through emotional resilience, self-confidence, authenticity, and personal agency. Using Kabeer’s framework, the discourse represents empowerment through resources, agency, achievements, and disempowerment, with agency emerging as the dominant dimension. However, the campaign also presents ambivalent representations in which empowerment is accompanied by insecurity, emotional regulation, and subtle expectations toward femininity. The study demonstrate that empowerment is framed as internal psychological transformation rather than structural social change, reflecting a postfeminist and depolitization discourse that individualizes women’s struggles and commodifies emotional experiences. This research showing how Appraisal subsystems operate to construct ideological meanings. It also uses Critical Discourse Analysis by revealing how evaluative language functions ideologically in constructing women’s empowerment within contemporary beauty advertising discourse.